Reduced discomfort during high-definition transcutaneous stimulation using 6% benzocaine - Guleyupoglu, Berkan; Febles, Nicole; Minhas, Preet; Hahn, Christoph; Bikson, Marom (Frontiers in Neuroengineering, 2014)
Abstract Background High-Definition transcranial Direct Current Stimulation (HD-tDCS) allows for non-invasive neuromodulation using an array of compact (approximately 1 cm2 contact area) “High-Definition” (HD) electrodes, as compared to conventional tDCS (which uses two large pads that are approximately 35cm2). In a previous transcutaneous study, we developed and validated designs for HD electrodes that reduce discomfort over >20 min session with 2 mA electrode current. Objective The purpose of this study was to investigate the use of a chemical pretreatment with 6% benzocaine (topical numbing agent) to further reduce subjective discomfort during transcutaneous stimulation and to allow for better sham controlled studies. Methods Pre-treatment with 6% benzocaine was compared with control (no pretreatment) for 22 minutes 2 mA of stimulation, with either CCNY-4 or Lectron II electroconductive gel, for both cathodal and anodal transcutaneous (forearm) stimulation (8 different combinations). Results Results show that for all conditions and polarities tested, stimulation with HD electrodes is safe and well tolerated and that pretreatment further reduced subjective discomfort. Conclusion Pretreatment with a mild analgesic reduces discomfort during HD-tDCS.